2007
DOI: 10.1590/s0034-72992007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Zonas mortas na cóclea em freqüências altas: implicações no processo de adaptação de prótese auditivas

Abstract: Em perdas auditivas de grau moderado a severo nas freqüências altas, a lesão coclear pode estar relacionada a "zonas mortas", regiões onde as células ciliadas internas e/ou neurônios adjacentes não são funcionais. OBJETIVO: Avaliar o reconhecimento de fala em pacientes com e sem zonas mortas na cóclea em freqüências altas. MATERIAL e MÉTODO: Estudo clínico e experimental de 30 indivíduos adultos, distribuídos em dois grupos: grupo 1 - 15 indivíduos sem zonas mortas, e grupo 2 - 15 com zonas mortas na cóclea. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…These patients usually have normal or almost normal hearing sensitivity in low and medium frequencies and were elected as candidates with restrictions for the use of amplification due to technological limitations (1) and to poor speech perception in noisy environments, once high-frequency amplification is not enough to provide good audibility of speech sounds and cannot be reused because of organic limitations (2) . In view of this, some researchers recommend the prescription of little or none amplification in high frequencies during adaptation of hearing aids for patients with steeply sloping hearing loss (3,4) . Conversely, it is known that information input at high frequencies can significantly improve speech perception, especially in noisy environments (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…These patients usually have normal or almost normal hearing sensitivity in low and medium frequencies and were elected as candidates with restrictions for the use of amplification due to technological limitations (1) and to poor speech perception in noisy environments, once high-frequency amplification is not enough to provide good audibility of speech sounds and cannot be reused because of organic limitations (2) . In view of this, some researchers recommend the prescription of little or none amplification in high frequencies during adaptation of hearing aids for patients with steeply sloping hearing loss (3,4) . Conversely, it is known that information input at high frequencies can significantly improve speech perception, especially in noisy environments (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…In the studies carried out by Baer, Moore and Kluk (2002)11, Vestergaard (2003) 12 , Gordo (2004) 13 and Almeida and Buzo (2005) 14 , cochlear dead zones diagnosis was carried out through the TEN test, and the authors did not find difficulties to perform the test, and the results found were reliable and matched the theoretical assumptions related to the presence of cochlear dead zones. In the studies carried out by Baer, Moore and Kluk (2002) 11 , Vestergaard (2003) 12 and Gordo (2004) 13 , there are references as to speech recognition, which is the main goal of the individual eligible to the use of hearing aids, and showed the importance of diagnosing dead zones in the cochlea: sound amplification is avoided in this region, and speech recognition improves.…”
Section: Discussionmentioning
confidence: 76%
“…Gordo (2004) 14 applied the TEN (HL) test in thirty adult individuals with bilateral descending sensorineural hearing loss. He used a two channel audiometer to control pure tone and noise separately, connected to a CD player.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The amplification of sounds in the frequency range that corresponds to the dead regions does not result in benefit and may even impair speech intelligibility. Therefore, some authors recommend caution in high frequencies amplification when hearing threshold is above 55 dB HL (3,4).…”
Section: Introductionmentioning
confidence: 99%